Mineralogical, geochemical, and magnetic susceptibility variations in the loess-paleosol sequence from Pattan, Kashmir Valley, India record an enhanced Indian summer monsoon around 35 ka. (10th April 2022) - Tauseef, Mohammad; Ray, Esha; Paul, Debajyoti; Malik, Javed N.; Ahmad, Ishtiaq
Abstract: We present multi-proxy records of bulk chemistry, clay mineralogy, stable isotope composition of soil organic matter (δ 13 CSOM ) and pedogenic carbonate (δ 18 OSC ), and mineral magnetic parameters of a loess-paleosol sequence from Kashmir Valley, India, to infer paleoclimate and paleovegetation during Late Pleistocene. 14 C AMS dating brackets the age of paleosols between 40 and 19.6 ka and suggests loess to be > 40 ka. Our study shows that a cold/dry climate prevailed at >40 ka (Late Pleistocene), during which the loess accumulation took place, and a warm/humid climate after that led to the development of soil units, with a prominent warm/humid phase around 35 ka. The range of Chemical Index of Alteration (72–78) and significant amounts of illite and chlorite in the section indicate moderate weathering. High kaolinite content, low chlorite, increased K/C, I/C, K/(I + C) ratio, and presence of poorly crystalline and Al-rich illite by ∼36 ka indicates increasing weathering intensity, likely due to an enhanced Indian Summer Monsoon (ISM). High magnetic susceptibility during 35–32 ka indicates enhanced pedogenesis due to a warm-humid climate. Paleotemperature estimates reveal a relatively warmer (by ∼7 °C) climate during pedogenesis than that at >40 ka. δ 13 CSOM values (−17‰ to −22.2‰) suggest C3 plants dominated the Kashmir Valley through the Late Pleistocene, however, a short period of enhanced summer monsoon at ∼35 ka favored C4 plant growth. The paleoclimate variability in the loess-paleosol sequence presented here agrees with the Guliya Ice Core δ 18 O record and high lake water levels in the Tibetan Plateau.